Strengthening the Mentality of Educators with the Independent Learning Curriculum in the Era of Society 5.0 - Burju Ruth; Rima Novia Ulfa (International Journal of Management, Innovation, and Education, 2025)
This study aims to explain the strengthening between the mentality of educators and the Merdeka Belajar Curriculum in the era of Society 5.0. An individual's view of their abilities and potential, with the belief that abilities can be developed through continuous effort, practice, and learning experiences. Meanwhile, the Merdeka Belajar Curriculum authorizes schools to design a curriculum that is responsive to the needs and potential of students. The research method used in this research is a descriptive qualitative approach by conducting literature studies and conceptual analysis. This research combines the concepts of mentality and Merdeka Belajar Curriculum to identify the relationship between the two in the Society 5.0 era. The data collected will be analyzed thematically to gain a comprehensive understanding of the relevance and practical implications of combining these two concepts in today's educational context. The results of this study will provide insight into how the implementation of mentality in the Merdeka Belajar Curriculum in the era of Society 5.0 and can develop adaptability and innovation in the independent learning curriculum in the era of Society 5.0.